Religious Development Management in Forming the Character of Criminers - Ahmad Nawawi Abdurrauf; Iim Wasliman; M. Andriana Gaffar; Mustatul Anwar (UIN Sunan Gunung Djati Bandung, 2019)
Management of religious guidance in shaping the character of prisoners is a renewal, refinement or effort of action or activity carried out in an integrated, efficient and effective manner to obtain better results. If this guidance activity is carried out on prisoners, then religious guidance will give meaning to the prisoner to be faithful, knowledgeable and have a noble character in life and life. The process of forming good characters must be in accordance with the basis for the formation of good characters itself, namely the Al-Qur'an and the life and life examples of the Prophet Muhammad SAW. Al-Qur'an is the Word of Allah SWT in which it provides guidance for humans in various aspects, one of which is about guidelines for behavior so that humans can distinguish between good and bad.